2017
DOI: 10.1002/clc.22810
|View full text |Cite
|
Sign up to set email alerts
|

Appropriateness vs value: Echocardiography in primary care

Abstract: Background Despite efforts targeting the growth of healthcare spending within the United States, the current increase in expenditures remains a widespread systemic issue. The overuse of healthcare testing has previously been identified as a modifiable contributing factor. One such test, echocardiography, has seen a continuous increase in its rate of use. This test is frequently ordered by primary‐care physicians. Hypothesis In the setting of a low likelihood of disease, echocardiography does not substantially … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 21 publications
0
15
0
1
Order By: Relevance
“…Studies on the adult appropriate use criteria have shown that even when echocardiograms were done for "appropriate" indications, the diagnostic yield and management changes were low. 6 This study found similar outcomes with only minor abnormalities that do not warrant intervention in the echocardiograms ordered for indications rated "appropriate. "…”
Section: Discussionmentioning
confidence: 54%
“…Studies on the adult appropriate use criteria have shown that even when echocardiograms were done for "appropriate" indications, the diagnostic yield and management changes were low. 6 This study found similar outcomes with only minor abnormalities that do not warrant intervention in the echocardiograms ordered for indications rated "appropriate. "…”
Section: Discussionmentioning
confidence: 54%
“…Furthermore, there is often limited capacity for performing an echocardiogram in a timely manner. Even though the majority of echocardiographic studies ordered in the primary care setting appear to be appropriate, only about 20% of patient abnormalities are detected and only 2.5% findings were consistent with the suspected diagnosis and led to a change in patient management (65). Generally, echocardiographic screening should be restricted to symptomatic patients in order to increase the likelihood of detecting relevant cardiac pathologies (66).…”
Section: Echocardiographic As-screening-innovative Conceptsmentioning
confidence: 99%
“…Echocardiography (echo) remains one of the most used imaging modalities in clinical practice, providing incremental information with low risk to the patient by employing ultrasound technology 1,2 . The availability of portable and affordable machines has allowed echocardiography to go beyond the frontiers of specialized centers, and its indications have progressively increased, being frequently ordered by primary-care physicians 3,4 . In response to marked increases in utilization of echocardiography, the delay in its access is inevitable.…”
Section: Introductionmentioning
confidence: 99%
“…The first consideration of healthcare providers is that the waiting list is a direct measure of the need for medicals services, and that the size of the list is directly related to the need. However, in a setting of low likelihood of cardiovascular disease, echocardiography does not substantially change cardiovascular therapeutics, even if appropriately ordered 4 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation